Teacher’s Questioning to Promote High Order Thinking Skills in EFL Learning (A Case Study at Christian High School YSKI Semarang) - Susilowati, Nunung; Hartono, Rudi; Astuti, Puji (English Education Journal, 2020)
In the learning process, teachers should pose some questions in order to check what has been learnt and understood, to help them review previous learning, and assess whether students are ready or not to move forward and learn new information. Regarding that statement, questioning section in the learning process is important. The aim of this research was to find out how the teachers use the questioning section in the learning process to promote the students’ high order thinking skills which are divided into three skills that are analysing, evaluating and creating skill. This study implied case study research. The instruments used in this research were observation checklist, recording, interview and questionnaire. The main data was the teachers’ recording in the learning process. The subjects of this study were three teachers of a religion-based high school in Semarang, Central Java. and the students of that school. The findings of the study showed that the teachers used questioning section in their learning process. The kinds of questions used were mostly open questions and close question or yes/no questions. Those questions were used in order to make the students think more critically. The teachers think that high order thinking skill is so important for the students so they applied those skills maximally in the learning process and by questioning, the teacher could get some advantages such as they could assess the students and also know the students understanding toward the material given. It can be concluded that the use of teacher’s questioning could be a tool to promote students’ high order thinking skills in EFL learning. It is also suggested for the teachers to use more questioning section in the learning process.